2014
DOI: 10.1177/0018726714541489
|View full text |Cite
|
Sign up to set email alerts
|

Global ends, local means: Cross-national homogeneity in professional service firms

Abstract: This version is available at https://strathprints.strath.ac.uk/50987/ Strathprints is designed to allow users to access the research output of the University of Strathclyde. Unless otherwise explicitly stated on the manuscript, Copyright © and Moral Rights for the papers on this site are retained by the individual authors and/or other copyright owners. Please check the manuscript for details of any other licences that may have been applied. You may not engage in further distribution of the material for any pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
84
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(86 citation statements)
references
References 63 publications
(113 reference statements)
0
84
0
2
Order By: Relevance
“…By not taking cognizance of how even very similar types of organization can behave very differently in different national contexts (Maurice et al, 1980), PSF research can therefore be accused of universalizing a particular. Even the limited cross-national comparative work in this area has largely restricted itself to Western contexts (see, for example, Boussebaa et al 2012;Muzio 2014, 2016;Muzio and Faulconbridge 2013;Smets et al 2012;Spence et al 2015). There is virtually no research exploring how PSFs operate in Asia.…”
Section: Rq1: What Form Does Symbolic Capital Take In Psfs In Differementioning
confidence: 99%
See 1 more Smart Citation
“…By not taking cognizance of how even very similar types of organization can behave very differently in different national contexts (Maurice et al, 1980), PSF research can therefore be accused of universalizing a particular. Even the limited cross-national comparative work in this area has largely restricted itself to Western contexts (see, for example, Boussebaa et al 2012;Muzio 2014, 2016;Muzio and Faulconbridge 2013;Smets et al 2012;Spence et al 2015). There is virtually no research exploring how PSFs operate in Asia.…”
Section: Rq1: What Form Does Symbolic Capital Take In Psfs In Differementioning
confidence: 99%
“…Cultural capital itself takes a variety of forms and is a key aspect of how actors position themselves within fields (Bourdieu 1986). Professional and University credentials, for example, constitute institutionalized cultural capital although it has been shown that even in Western contexts there is variation in the value placed upon degrees from specific educational institutions, with French Big 4 firms being much more elitist than their Spanish, British or Canadian counterparts (Spence et al 2015). It is unclear to what extent educational credentials are more or less valued by Big 4 firms in Asia, although wider literature on the educational systems in Japan and…”
Section: Extant Literature On Psfs In China and Japan Offers Little Gmentioning
confidence: 99%
“…While Spence et al (2015) convincingly demonstrate that economic drivers within the audit field are more hegemonic than is sometimes presupposed, they also note that "it may be well be the case that complexity … reign(s) during times of institutional change" (p. 3). The intersection of auditing and other domains (e.g., professional sport, travel, government, and the environment) do introduce unfamiliar norms, expectations and the 'rules of the game', which make jockeying for dominant positioning, even for the highly powerful and influential PSFs, complex and challenging.…”
Section: Discussionmentioning
confidence: 97%
“…[ INSERT TABLE 4] In line with Spence et al (2015), we expect accounting elites to pursue new opportunities where they believe sufficient opportunities for economic capital accumulation and/or enhancing reputation and thus symbolic capital are on offer. Consequently, Big-4…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation